2023
DOI: 10.1038/s41388-023-02892-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of CDK9 in triple negative breast cancer

Ebtihal H. Mustafa,
Geraldine Laven-Law,
Zoya Kikhtyak
et al.

Abstract: Targeted therapy for triple-negative breast cancers (TNBC) remains a clinical challenge due to tumour heterogeneity. Since TNBC have key features of transcriptionally addicted cancers, targeting transcription via regulators such as cyclin-dependent kinase 9 (CDK9) has potential as a therapeutic strategy. Herein, we preclinically tested a new selective CDK9 inhibitor (CDDD11-8) in TNBC using cell line, patient-derived organoid, and patient-derived explant models. In vitro, CDDD11-8 dose-dependently inhibited pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Despite several significant advancements in targeting CDKs as novel approaches and promising treatment options against TNBC (Figure B,C; compound 1 – 6 ), there remains a shortage of CDK9 modulators specifically designed for TNBC treatment, and most of these inhibitors either exhibit only moderate potency or target other subtypes of CDKs (especially CDK2, a cell cycle-related CDK with 40% sequence identity to CDK9). For example, dinaciclib (also named SCH727965 or MK-7965), which progressed into three TNBC-related clinical trials (phase 1 or phase 2; ClinicalTrials.gov ID: NCT00732810, NCT01624441, NCT01676753), have similar inhibitory activity against CDK2 and CDK9 (IC 50 = 1 and 4 nM, respectively); fadraciclib (CYC065), being tested in an ongoing clinical trial on advanced solid tumors, including TNBC (phase 1/2; ClinicalTrials.gov ID: NCT04983810), also targets both CDK2 and CDK9 (IC 50 = 5 and 26 nM, respectively) . Indeed, off-target inhibition might result in side effects and unexpected toxicity, thereby narrowing the therapeutic window and compromising the potential for developing targeted therapeutics; principally, the development of selective inhibitors offers various benefits, including providing specific insight into the mechanism of action, refining patient selection criteria, and facilitating the establishment of a specific therapeutic window .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite several significant advancements in targeting CDKs as novel approaches and promising treatment options against TNBC (Figure B,C; compound 1 – 6 ), there remains a shortage of CDK9 modulators specifically designed for TNBC treatment, and most of these inhibitors either exhibit only moderate potency or target other subtypes of CDKs (especially CDK2, a cell cycle-related CDK with 40% sequence identity to CDK9). For example, dinaciclib (also named SCH727965 or MK-7965), which progressed into three TNBC-related clinical trials (phase 1 or phase 2; ClinicalTrials.gov ID: NCT00732810, NCT01624441, NCT01676753), have similar inhibitory activity against CDK2 and CDK9 (IC 50 = 1 and 4 nM, respectively); fadraciclib (CYC065), being tested in an ongoing clinical trial on advanced solid tumors, including TNBC (phase 1/2; ClinicalTrials.gov ID: NCT04983810), also targets both CDK2 and CDK9 (IC 50 = 5 and 26 nM, respectively) . Indeed, off-target inhibition might result in side effects and unexpected toxicity, thereby narrowing the therapeutic window and compromising the potential for developing targeted therapeutics; principally, the development of selective inhibitors offers various benefits, including providing specific insight into the mechanism of action, refining patient selection criteria, and facilitating the establishment of a specific therapeutic window .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our recent research demonstrates that selectively targeted degradation of CDK9 via Proteolysis Targeting Chimeras (PROTACs) can also effectively downregulate the downstream target MCL 1 - at the transcriptional level, leading to apoptosis in TNBC cells . While this endeavor is still at an early stage, recent studies by others and us have suggested that disrupting CDK9 activity led to effective inhibition of proliferation in both in vitro and in vivo TNBC models, , highlighting that targeting CDK9 holds promise for TNBC treatment.…”
Section: Introductionmentioning
confidence: 99%